2018
DOI: 10.32007/jfacmedbagdad.v60i1.44
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Oral Contraception on Coagulation Profiles in Women Attending Fertility Control Clinic in Baqubah City- Iraq

Abstract: Background: Use of oral contraception has been associated with an increased abnormalities of lipid and carbohydrate metabolism as well as hemostatic variables at baseline (increased plasma levels of factor VII, factor X, fibrinogen and of D-dimers).Objectives: To evaluate the effect of oral contraceptive pills (combined pills) on coagulation tests,prothrombin time (PT), activated partial thromboplastin time (APTT), and fibrinogen level.Patients and methods: This is a descriptive cross sectional study which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Regarding the effect of contraceptives use duration on the mean of PT, APTT and platelet count results, statistical analysis revealed that there were insignificant difference in mean of PT and platelet count with P.value of (0.92, 0.65) respectively, while that there was significant difference in mean APTT result with P.value of (0.007). This results was not similar to the results of study which done by Sawsan Salman and his colleagues (16) Also regarding the effect of contraceptives type on the mean of PT, APTT and platelet count), statistical analysis revealed that there were significant difference in PT, APTT and Platelet results between usage of combined oral contraceptive (COC) and usage of progestin only pills (POP)mini pills), with P.value of (0.03, 0.01 and 0.007) respectively. The results of PT and APTT were disagreeing with results of Mohieldin Elsayid and colleagues.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Regarding the effect of contraceptives use duration on the mean of PT, APTT and platelet count results, statistical analysis revealed that there were insignificant difference in mean of PT and platelet count with P.value of (0.92, 0.65) respectively, while that there was significant difference in mean APTT result with P.value of (0.007). This results was not similar to the results of study which done by Sawsan Salman and his colleagues (16) Also regarding the effect of contraceptives type on the mean of PT, APTT and platelet count), statistical analysis revealed that there were significant difference in PT, APTT and Platelet results between usage of combined oral contraceptive (COC) and usage of progestin only pills (POP)mini pills), with P.value of (0.03, 0.01 and 0.007) respectively. The results of PT and APTT were disagreeing with results of Mohieldin Elsayid and colleagues.…”
Section: Discussioncontrasting
confidence: 92%
“…While PT values don't showed significant variation with P.value of (0.35), this result was similar to results of study done by Mohieldin Elsayid and colleagues. (14) Also this results was not similar the results of study which done by Sawsan Salman and his colleagues (16) which noted that there was no significant variation in APPT, while agreed regarding PT value.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation